Teologie dell'Antico Testamento - Fischer, Georg (San Paolo ‒ Gregorian & Biblical Press, 2015)
This volume illustrates the different images of God in the books of the Old Testament. The single writings are considered synchronically in their final version. They speak in totally different ways about God and present a fascinating variety of theologies.